PENERAPAN TEORI BEHAVIORISME B.F. SKINNER DALAM PEMBENTUKAN DISIPLIN DAN KEMAMPUAN BERBAHASA ARAB SANTRI DI PONDOK PESANTREN AHLUL QUR'AN KABUPATEN POLEWALI MANDAR - Afrian Cahya Utama; Rasdiana; Jelita; Masitha Almukarramah; Aan Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of B.F. Skinner's behaviorism theory, particularly the principle of operant conditioning, in shaping the discipline and Arabic language proficiency of santri (students) at Pondok Pesantren Ahlul Qur'an. Discipline formation and Arabic mastery remain persistent challenges in many Indonesian pesantren, where habituation is often applied intuitively without being grounded in an explicit learning-theory framework, leaving a gap between everyday practice and its theoretical explanation. This research addresses that gap through a descriptive qualitative case study. Data were collected through one week of participatory observation of the daily routine, the learning system, and the twenty-four-hour Arabic language environment, complemented by brief interviews and documentation, and analyzed using the Miles and Huberman interactive model of data reduction, display, and conclusion drawing. The findings show that the strictly structured daily schedule functions as a repeated conditioning stimulus, the twenty-four-hour Arabic-only environment produces sustained language conditioning, and the three-month shaping process for new santri builds linguistic competence gradually from vocabulary to simple conversation. Positive reinforcement, such as verbal appreciation, delegation to inter-institutional Arabic competitions, and graduation awards, works together with positive and negative punishment, such as physical correction and the reduction of leave privileges, to consistently regulate santri behavior. These findings confirm and extend prior studies on behaviorism in Arabic-language pesantren environments, and they carry practical implications for the design of discipline and language-immersion programs within Islamic Religious Education.